Pragmatic Transfer in Intermediate Japanese Learners' Apology Speech Act - Nuria Haristiani; Devy Christinawati; Sudjianto Sudjianto (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to investigate the apology speech act strategy employed by Japanese language learners at the intermediate level and the pragmatic transfer from L1 to L2 that occurs. The data for this study were gathered using the Discourse Completion Test (DCT), which examined four apology situations focusing on the relationships with the interlocutors. The subjects of this study were 53 intermediate Japanese learners. The collected data were then classified into eight strategies or semantic formulas. The pragmatic transfer in the learner's expression was divided into pragmalinguistic transfer and sociopragmatic transfer. This study found that several factors were related to the pragmatic transfer. First, learners translate L1 phrases literally to the L2, which leads to pragmalinguistic transfer. Second, many variations and combinations in Japanese words and sentences are difficult compared with expressions in Indonesian, especially in the